Răspuns:
Explicație pas cu pas:
a)
2*3*(-1)= 6*(-1)=-6
9*(-5)*(-3)= (-45)*(-3)=135
(-4)*2*(-5)= (-8)*(-5)= 40
(-9)*(-3)*(-2)= (-9)*6= -54
7*(-2)*(-5)= 7*10= 70
(-9)*2*(-3)= 27*2= 54
(-5)*8*(-2)=10*8= 80
(-6)*(-4)*10= 24*10= 240
b)
(-5)*2*(-3)*(-1)=(-10)*3= -30
8*3*(-5)*2= 24* (-10)= -240
(-7)*2*(-4)*3= (-14)* (-12)= 168
-(-4)*(-3)*(-5)*1= 4* (-3)* (-5)= 4* 15= 60
8*(-5)*(-3)*10= (-40)*(-30)= 1200
(-6)*4*7*6= (-24)*42= -1008
(-10)*9*3*(-5)*(-1)= (-90)*(-15)*(-1)= 1350*(-1)= -1350
(-6)*(-4)*(-9)*(-2)= 24*18=432
5*(-3)*4*2*0=0